(untitled) (Global Journal of Medical Research, 2024)
Objective This study aimed to investigate the intricate physical systemic and stomatological characteristics of individuals with Down Syndrome a condition characterized by trisomy 21 known for its unique features that can influence dental treatment protocols Materials and Methods A descriptive observational cross-sectional study was conducted on a convenient sample of 42 individuals aged between 0 and 18 years with Down Syndrome The participants underwent structured interviews with caregivers medical history assessments physical examinations to evaluate systemic and physical conditions as well as oral health evaluations encompassing the visible biofilm index gingival condition ICDAS International Caries Detection and Assessment System and INI Invasive Treatment Need Index Results The research sample revealed a plethora of characteristics including a high prevalence of respiratory diseases 71 4 overweight or obesity 59 5 heart disease 57 1 obstructive sleep apnea 54 8 behavioral challenges during care 61 9 cleaning difficulties 40 5 macroglossia 69 bruxism 61 9 suboptimal biofilm index varying degrees of gingivitis and a low incidence of dental caries Conclusion Patients with Down Syndrome showcased specific physical systemic and stomatological traits that can markedly influence oral health status oral hygiene routines and behavior during dental procedures This emphasizes the critical importance of dentists possessing an in-depth understanding to implement tailored management strategies aimed at enhancing the overall health and well-being of these unique individuals